Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pengguna Kartu Halo Pada Grapari Telkomsel Pekanbaru - Retna Ridaningsih; Sri Restuti; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is motivated by the importance of maintaining the relationship between consumers and companies to the survival of a company. To make and gain the loyalty of consumers, in need of a lot of the supporting factors of these company. The important factor is the quality of service.Likewise with PT. Telkomsel has the largest subscriber in Indonesia should maintain and improve the highest satisfaction for their customers.After a literature review , and preparation of hypotheses , data were collected through questionnaire method against 80 respondents are all KartuHalo customers. The technique used in this sampling is accidental sampling where the sample is taken with certain considerations and dealing with the problems studied are a customer who came to pay the bill in Grapari kartu HALO. After that analysis from the data obtained using multiple linear regression analysis. This analysis includes the validity test, reliability test, multiple linear regression analysis, hypothesis testing via the F test and t test, and coefficient of determination (R2).The results indicate that tangible, reliability, responsiveness, assurance and empathy influence on Grapari Telkomsel customer satisfaction. Where simultaneous test results showed all the independent variables have a significant effect on the dependent variable, it can be seen from F Calculate 30.907 > F table 2.33.While partially variable, the variable responsiveness, assurance and empathy strong influence in which the t value of each variable is 5,415,4,730 and 3,643 greater than t table 2,29.While the tangible variables and variable reliability has a weak effect because t each variable are 1.563 and 2.211 is smaller than t table that is equal to 2.29. The coefficient of determination (R2) shows the independent variables contributed 65.4%.Keywords :Assurance, Customer Satisfaction, Emphaty, Reliability, Responsiveness, Tangible